The Fiscal Implications of Trade Liberalization. (IMF Working Papers; Working Paper ;, 1988)
Trade liberalization affects not only the external sector, production, and prices, but also the fiscal balance, through changes in tariff revenue, and through the sensitivity of the budget to induced changes in the exchange rate and in the level and distribution of income and employment. This paper discusses the effects of liberalization on the budget, which may differ in the short- and long-run. The short-run cost of adjustment to open trade could force the government to reverse the liberalization even if longer-term benefits could be realized. Long-run budget gains are more likely when the tax and transfer systems are broad, neutral, and efficiently administered.